Change of State: Information, Policy, and Power - Michel Thiollent (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
Cambridge-Mass: The MIT Press, 2006